Effects of continuous variation in vertical and lateral herkogamy on reproductive success in Euphorbia fischeriana (Euphorbiaceae) - Xiang Zhao; Guang Yang; Qinzheng Hou; Wenrui Min; Taihong Wang; Xiaoyan Bao (Ecology and Evolution, 2023)
Abstract Continuous variation in herkogamy has been well reported, however, less attention has been paid to the phenomena that the consecutive expression of two types of herkogamy in the same flower. Euphorbia fischeriana, which have both vertical and lateral herkogamy, show vertical herkogamy during the female phase. However, their gynophores bend to one side with the male phase and show lateral herkogamy. In this study, we observed the effect of successive sexual organs movement on variation in herkogamy traits. By artificially manipulating the flower to present gynophore straightened in the floral center or bend to one side, we attempted to investigate whether herkogamy movement affects pollinator access efficiency, pollen removal and deposition, and seed set ratio. Furthermore, we conducted artificial pollination in the female phase to evaluate the effect of changes in pollination environment on the variations in herkogamy traits. The results showed that gynophore straightened in female phase favors pollen deposition, whereas gynophore bending in male phase was conducive to the removal of pollen. Visitation frequency, pollen deposition and removal, and seed set ratio decreased significantly when the gynophore movement was manipulated. Finally, the bending of gynophore was obviously promoted by pollination. Therefore, the continuous variation of herkogamy in the same flower of E. fischeriana caused by the bending of the gynophore could improve the accuracy of pollination and avoid the interference of the ovary with access efficiency. That may be an adaptive strategy when pollinators are scarce. Furthermore, our study also provides good support for the hypothesis that variations in herkogamy traits are strongly selected by differences in pollination environments.